Effect of pre-feeding forage treatments, harvesting stage, and animal type on preference of tagasaste (Chamaecytisus palmensis) - Assefa, G.; Kijora, C.; Kehaliew, A.; Sonder, Kai; Peters, Kurt J. (Springer, 2012)
Tagasaste (Chamaecytisus palmensis), a multipurpose fodder tree, is highly productive in the tropical highlands. The forage has high crude protein (CP) concentrations but is reported to have low intake by ruminants. This study investigated the effects of plant harvest stage and feeding management (wilted, dried and fresh) on levels of tannins in tagasaste and on preference and intake by Menz sheep and cattle fed during the dry season. The treatments were (1) fresh tagasaste, (2) wilted tagasaste, (3) dried tagasaste and (4) native hay. There were three preference experiments using sheep (20.2 ± 0.66 kg) to investigate intake under ad libitum or restricted offering of the forages, and to assess effect of harvest age (6- or 10-month regrowth age) on ad libitum intake. In two further experiments ad libitum offerings of the forages were evaluated using young steers (131.2 ± 19.6 kg) and heifers (156.3 ± 5.4 kg). The CP (201 g/kg), hydrolysable tannin (150.2 g/kg) and condensed tannin (8. 97abs measured as absorbance at 550 nm wavelength/g NDF) contents of tagasaste forage were not affected by the physical treatments and harvesting stage. When fed ad libitum, sheep preferred (P < 0.01) fresh forage to wilted or dry tagasaste (24.5 vs. 22.9 and 7.9 g dry matter (DM)/kg metabolic body weight (MBW). The restricted offering increased intake of the less preferred dried form. Regrowth age (6 vs.10 months) did not affect sheep preference. Unlike sheep, steers and heifers preferred (P < 0.01) dried tagasaste rather than the fresh or wilted forage. Animal preference and intake were affected by the preparation method of the forage, but not by regrowth age. Methods to improve intake (for cattle), effects of long-term feeding and evaluation on the subsequent effect of anti-nutritional compounds during digestion and animal performance should be further investigated.